Safety Confidence of River Bank Protection Works Under Long-Line Effect - Quang Hung Nguyen, Lan Huong Nguyen, Van Quan Tran (International Journal of Advanced Science and Technology, 2020)
A large part of Vietnam’s annual investment has been allocated in bank protection works for Red, Thai Binh and Lo rivers to mitigate life and property damages and losses caused by bank erosion and landslides. Slope revetment and vertical revetment are effective solutions to enhance the river bank stability. The research introduced different types of revetments built on big rivers in Vietnam, their problems and the considered impacts. The authors applied random theory-based method of revetment safety probability in analyzing the confidence of revetment on Red River right bank reach that runs crossing Lao Cai city. The calculations showed that the revetment met Russia’s confidence standards, regardless the effect of the revetment’s length and it’s likely in danger under the effect of 992.5m long revetment; revetment reach No. 3’ impact on the system’s safety was the most significant. The analysis of the confidence of different revetment reaches and the impact of random elements on safety of the revetment system provides an effective solution if revetment upgrades or repairs are required.